2017
DOI: 10.2174/1875399x01710010286
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Biomechanical Fatigue Responses in Karate: A Case Study

Abstract: Knowledge of the fatigue process in karate sport is essential to improve the performance of top athletes. The physiological and biomechanical behavior during the Karate Specific Aerobic Test (KSAT) fatigue protocol in karate was investigated. PCR, lactate, glucose and cortisol were collected before and after the fatigue protocol application in karate, besides that, and heart rate and technical speed were measured. The results indicated increase in C protein reactive (60%), creatine kinase (25%), cortisol (30%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…This would occur due to one of the factors is not having enough physical activity. During the fatigue cycle, the dynamic speed can experience many changes and can compromise the performance of the athletes (Urbinati et al, 2017). However, pertain to martial arts, it has been revealed that attacking fighting style, would enhance the ability to function more, reduce fatigue and anxiety plus presence of psychological comfort (Korobeynikov et al, 2015;Iermakov et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This would occur due to one of the factors is not having enough physical activity. During the fatigue cycle, the dynamic speed can experience many changes and can compromise the performance of the athletes (Urbinati et al, 2017). However, pertain to martial arts, it has been revealed that attacking fighting style, would enhance the ability to function more, reduce fatigue and anxiety plus presence of psychological comfort (Korobeynikov et al, 2015;Iermakov et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A few types of research have been conducted in the domain of Karate competitions (Kumite). Previous studies in combat sports have been done on Kata biomechanics and basic techniques (3,4), on injuries (5,6), on psychology (7,8), and physiology (9,10). Beekley and Tabben noted that performance specification does not depend on combat sports and that winning and success need a combination of technique, power, aerobic fitness, and speed (11,12).…”
Section: Introductionmentioning
confidence: 99%